Adjuvant Chemotherapy in pT2N0M0 Gastric Cancer: Findings From a Retrospective Study - Yu Mei; Xijia Feng; Tienan Feng; Min Yan; Zhenggang Zhu; Tian Li; Zhenglun Zhu (Frontiers Media S.A., 2022)
Background: There is no global consensus on adjuvant chemotherapy (ACT) for pT2N0M0 gastric cancer. We conducted a retrospective study to reveal the role of ACT in such patients.Methods: Patients with pT2N0M0 gastric cancer who underwent radical resection with D2 lymphadenectomy for primary gastric cancer between January 2012 and May 2016 were included. Kaplan-Meier and Cox regression were used to evaluate overall survival (OS), disease-specific survival (DSS) and predictors of prognosis. Stratified analysis based on high-risk factors was conducted.Results: Of enrolled 307 patients, 111 patients underwent surgery alone and 196 patients received ACT. Surgery alone (HR = 2.913, 95% CI: 1.494-5.682, p = 0.002) and total gastrectomy (HR = 2.445, 95% CI: 1.279-4.675, p = 0.007) were independently associated with decreased OS. With the median follow-up of 73.1 months, the 5-year OS rate was 87.9% and 5-year DSS rate was 91.8%. Patients receiving ACT showed a better 5-year OS rate (92.9 vs. 79.3%, p < 0.001) and DSS rate (96.8 vs. 83.0%, p < 0.001) than patients underwent surgery alone. Patients receiving monotherapy (n = 130) had a relatively poor prognosis compared to patients receiving dual-drug (n = 66) without a significant difference (92.3 vs. 93.9%, p = 0.637). In patients without high-risk factors based on the Chinese Society of Clinical Oncology (CSCO) Guidelines, ACT also provided survival benefit (96.0 vs 82.9%, p = 0.038).Conclusions: ACT was accompanied with higher 5-year OS and DSS rates of patients with pT2N0M0 gastric cancer. Patients with pT2N0M0 gastric cancer, regardless of high-risk factors based on the CSCO guidelines, might be considered candidates for ACT. In regard to the therapy regimen, monotherapy might be the optimal choice, considering the adverse events.